Production of bio-coal based on empty fruit bunches by torrefaction method with fixed bed and tubular continuous reactors - Martin, Awaludin; Ginting, Yogie Rinaldy; Kurniawan, Iwan; Agusta, Dhiky Rahman; Khotimah, Nur (Universitas Mercu Buana, 2024)
Excessive use of fossil energy has negative impacts, which can cause climate change and environmental degradation. Thus, there is a need to find alternative, more sustainable energy sources. Biomass derived from Empty Fruit Bunch (EFB) waste is a newfound renewable energy source. However, its utilization is not optimal due to its low heating value and high chlorine (Cl) and potassium (K) content, which can interfere with combustion. EFB is washed with peat water to reduce potassium and chlorine content, and the torefaction process is used for combustion. This research aims to develop bio-coal production from empty fruit bunches using the torefaction method using fixed beds and continuous tubular reactors. The production process development also aims to obtain a larger production capacity than previous studies. This study uses varying weights of EFB produced into bio-coal, namely 250, 500 and 1000 grams, with a torefaction process temperature of 200°C for 30 minutes. As a result, the peat water flow rate decreased K, Cl and K2O content to the lowest content reduction value, which amounted to 8.31%, 0.42% and 3.96%, respectively. The heating value of bio-coal produced in a fixed bed reactor is 26,166 kJ/kg, while in a continuous tubular reactor, it is 21,720 kJ/kg. Based on these results, the fixed bed reactor shows a higher heating value than the continuous tubular reactor. The heating value obtained from these two types of reactors is comparable to sub-bituminous coal, which is usually used in steam power plants.